Comparison of the results of early, delayed and elective surgery in biliary pancreatitis - Abdülkadir BEDİRLİ and Erdoğan M. SÖZÜER and Ömer ŞAKRAK and Hülya BABAYİĞİT and; YILMAZ (Turkish Journal of Gastroenterology, 2019)
-